Criminal Law Countermeasures to Terrorist Activities in the Russian Federation and Abroad - MINYAZEVA, Tatiana F.; GAMIDOV, Rinat T. (Journal of Advanced Research in Law and Economics; Vol 6 No 2 (2015): JARLE Volume VI Issue 2(12) Summer 2015, 2016)
Terrorism is characterized by a wide variety of manifestations, that confronts the criminal law science and the legislator with difficult issues of clear definition of the criteria for the designation of one or other criminal activity as a terrorist one. Different countries fight this truly social evil in different ways. In this article the feasibility of criminal responsibility differentiation within main directions of the anti-terrorism efforts is discussed. The legislation on combatting terrorist activities in Russia, in the European Union and in the United States is analyzed, the authors study the global experience, identify the approaches to the establishment of the effective countermeasures to terrorist activities and other regulations, requiring the adjustment of the existing anti-terrorist legislation in terms of the elimination of a number of contained internal contradictions and gaps. In the presence of the obvious need for a balanced approach to the introduction of the new criminal offenses in the criminal law, while capable, in case of misjudgment, to result in excessive casuistry and artificial competition of regulations, it should to be noted in the conclusion, that it is very important for the criminal regulations to be stable, clear to use, grounded doctrinally and be socially and economically efficient. At the same time, the present situation requires a constant renewal, improvement and adjustment of the existing anti-terrorist legislation in the context of elimination of the present inconsistencies and gaps, in order to respond promptly to the challenges of the terrorist groups, and to protect people from terrorism.
Keywords: terrorism, combatting the terrorism, development of the legislation, comparison